Multivariate Procedures to Describe Clinical Staging of Melanoma - Manton, K. G.; Woodbury, M. A.; Wrigley, J. M.; Cohen, H. J. (Methods of Information in Medicine, 1991)
Analyzing multivariate clinical data to identify subclasses of patients being treated for a specific disease may improve patient management and increase understanding of the behavior of disease under clinical conditions. In some cases, patients have been classified on prognostic characteristics using standard risk assessment procedures (e.g.. Cox’ regression). This requires long term follow-up, differentiates patients only on attributes relevant to survival, and assumes that patients are sampled from a common population. Other approaches involve the use of clustering algorithms to classify patients into categories based on multiple clinical attributes. We illustrate the use of a multivariate statistical procedure to directly characterize patients on multiple clinical characteristics. The procedure is designed to analyze discrete response data with parameters representing individual differences within groups. Its use is illustrated for patients with Stage I melanoma in determining how age is related to treatment response in different patient groups.
Keywords: Stage I Melanoma; Fuzzy Sets; Grade of Membership; Disease Staging; Aging